2022
DOI: 10.1002/vzj2.20213
|View full text |Cite
|
Sign up to set email alerts
|

Fate and transport of Cryptosporidium parvum oocysts in repacked soil columns: Influence of soil properties and surfactant

Abstract: A series of laboratory experiments was performed to investigate the transport and retention of viable C. parvum oocysts in soil columns homogeneously packed with loamy sand soils (Lewiston and Greenson series) and sandy loam soils (Sparta and Gilford series), and under hydrologic conditions involving the presence of an anionic surfactant—Aerosol 22 in artificial rainfall. To characterize the effect of surfactant on the mobility of C. parvum oocysts in the soils used in this study, these results were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 290 publications
1
5
0
Order By: Relevance
“…Indeed, an increase in the negative zeta potential of sand was observed with an increase in the concentrations of anionic surfactant, which enhanced bacterial transport (Bai et al, 1997; Chen et al, 2004; Zhong et al, 2017). In their demonstration of the influence of Aerosol 22 upon the fate and transport of C. parvum oocysts in soils Darnault et al (2022) determined transport and retention of C. parvum oocysts in soil according to the physical and chemical parameters considered—soil texture, soil physics and chemistry, and surfactant. The result was a termination in either the enhancement or hinderance of C. parvum oocysts adsorption to soil particles, and their movement in soils.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, an increase in the negative zeta potential of sand was observed with an increase in the concentrations of anionic surfactant, which enhanced bacterial transport (Bai et al, 1997; Chen et al, 2004; Zhong et al, 2017). In their demonstration of the influence of Aerosol 22 upon the fate and transport of C. parvum oocysts in soils Darnault et al (2022) determined transport and retention of C. parvum oocysts in soil according to the physical and chemical parameters considered—soil texture, soil physics and chemistry, and surfactant. The result was a termination in either the enhancement or hinderance of C. parvum oocysts adsorption to soil particles, and their movement in soils.…”
Section: Discussionmentioning
confidence: 99%
“…The soils used in this study were collected as bulk samples from fallow and cultivated fields in Illinois and Utah, USA (Darnault et al, 2017; Darnault et al, 2022). Soils were air dried at 37°C, sieved in a 2 mm sieve and stored at room temperature in lidded buckets until used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The papers in this special section deal with (a) the deposition and release of clay colloids and nanoparticles in porous media, where it was shown that heavy metals enhanced the attachment of clay colloids and that attached clay colloids can be released by cation exchange or reduction of the solution ionic strength (Shi et al., 2022); (b) the colloidal transport of heavy metals in low‐advective‐velocity environmental systems, where it was shown that when the interaction between sorbed contaminants with colloidal particles are ignored, the contaminant concentrations in aqueous environments might be underestimated under low flow velocity conditions (Sengor & Unlu, 2022); (c) the fate and transport of Cryptosporidium parvum oocysts in porous media in the presence of surfactants, where it was shown that the presence of a surfactant could either increase or decrease the mobility of protozoa in porous media depending on the soil type (Darnault et al., 2022); (d) the cotransport of titanium dioxide nanoparticles and formaldehyde in saturated and unsaturated porous media, where it was shown that substantial retention of titanium dioxide nanoparticles occurs in both saturated and unsaturated porous media, and that the transport of formaldehyde was hindered in the presence of titanium dioxide nanoparticles, especially at high ionic strength (Chrysikopoulos & Fountouli, 2022); (e) the effects of microplastic on water dynamics in porous media, where it was concluded that microplastics at high concentrations can significantly hinder water infiltration (Cramer et al., 2022); and finally (f) the interfacial convections at the water–nonaqueous‐phase liquid interface in microfluidic systems, where it was shown that Marangoni, dissolution‐driven, and evaporation‐driven flow leads to enhanced mixing of phases in the vadose zone at nonaqueous‐phase liquid–water interfaces (Wismeth et al., 2022).…”
mentioning
confidence: 99%